A Highly Linear Low-Voltage Source-Degeneration Transconductor Based on Unity-Gain Buffer - 孔耀晖 刘爱荣 杨华中 (Tsinghua science and technology, 2009)
A complementary metal oxide semiconductor （CMOS） transconductor based on a high performance unity-gain buffer driving the degeneration resistor was used to obtain a highly linear voltage-to-current conversion with considerable reduction of the supply voltage. Simulations show that the transconductor using an 0.18-μm standard CMOS process with a 1.2-V supply voltage has less than -80 dB total harmonic distortion （THD） for a 1-MHz 0.4-Vp-p differential input signal. The third-order intermodulation is less than -63 dB for 0.25 Vp-p differential inputs at 1 MHz. The DC power consumption in the transconductor core is 240 μW. This topology is a feasible solution for low voltage and low power applications.